Asymmetric [4+2] cycloaddition of azlactones with dipolar copper–allenylidene intermediates for chiral 3,4-dhydroquinolin-2-one derivatives - Sun, Bing-Bing; Hu, Qing-Xian; Hu, Jia-Ming; Yu, Jie-Qiang; Jia, Jun; Wang, Xing-Wang (Tetrahedron letters, 2019)
[Display omitted] •Developing a high efficient enantioselective decarboxylative [4+2] cycloaddition.•Providing a series of enantio-enriched 3,4-dihydroquinolin-2-one derivatives in high yields.•Dipolar copper–allenylidenes as the key intermediates to react enolate azlactones. In this paper, a pybox-copper catalyzed enantioselective decarboxylative [4+2] cycloaddition reaction of ethynyl benzoxazinanones with azlactones has been developed, which provides optically active 3,4-dihydroquinolin-2-ones in high yields with good enantioselectivities and diastereoselectivities. In this transformation, the chiral dipolar copper–allenylidene intermediates are kinetically generated via decarboxylative ethynyl benzoxazinanones, followed by the attack of the enolate azlactones to form enantiomerically enriched 3,4-dihydroquinolin-2-one structures.